Electrochemical behaviors of Li-argyrodite-based all-solid-state batteries under deep-freezing conditions. Issue 100 (30th November 2018) - Choi, Sungjun; Jeon, Minjae; Kim, Byung-Kook; Sang, Byoung-In; Kim, Hyoungchul
Abstract : The electrochemical behavior of all-solid-state batteries in harsh environments was investigated and new insights for its low-temperature operation were provided. Abstract : We probe the electrochemical performance of Li-argyrodite-based all-solid-state batteries under deep-freezing conditions (−30 °C) using electrochemical impedance spectroscopy. The performance deterioration is mainly caused by the increased interfacial resistances of electrolyte and active materials resulting from the slow kinetics of Li-ion transport in solid materials at low temperatures.